On the relatively Pseudo-complement operation in finite RHAs - Minh, Hồ Anh; Nam, Huỳnh Văn (Journal of Computer Science and Cybernetics, 2016)
Refined hedge algebras were introduced and investigated by Ho & Nam in [6–9]. It is known [9] that every refined hedge algebra (RHA, for short) with a chair of the primary generators is a distributive lattice. In this paper we restrict our consideration to finite version of RHAs (see [7, 9]). It is shown that every finite RHA is a Heyting (pseudo-Boolean) algebra. Furthermore, some computing results for the relatively pseudo-complement operation in these algebras will be exhibited.